Assessing territorial impacts of the EU cohesion policy at the regional level: the case of Algarve - Medeiros, Eduardo (2019)
This article focuses on presenting the main territorial impacts of the projects approved under the auspices of the EU Cohesion Policy in Algarve (Portugal), over the last couple of decades (1990–2010). In general terms, it tunes up the TARGET_TIA methodology to assess the territorial impacts at the regional level. More concretely, it analyses the territorial impacts in the four main dimensions of territorial cohesion: socio-economic cohesion, environmental sustainability, territorial governance/cooperation and urban polycentricity. In syntheses, the territorial impacts of the EU Cohesion Policy in Algarve were moderately positive in stimulating regional development.